2015
DOI: 10.1007/s10980-015-0196-2
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent response of tropical wetland fish communities to changes in vegetation cover and habitat connectivity

Abstract: Context The replacement of native vegetation by exotic grasses for livestock production is driving landscape homogenization, habitat fragmentation and reducing connectivity between habitat patches in floodplains ecosystems. Objective In this context we examined how changes in native and exotic vegetation cover, connectivity and water depth affect the attributes of the small [standard length (SL) \ 80 mm as adults] and large-sized fish assemblages (SL C 80 mm as adults). MethodWe assessed the effects of water d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 89 publications
0
11
0
1
Order By: Relevance
“…The degree of hydrodynamic connectivity can determine both the assemblage and abundance of organisms in wetlands (Meynecke et al 2008; Fernandes et al 2015). The breaches at Blacklock provide considerable exchange with the adjacent embayment through which aquatic organisms can enter and leave the restoring marsh.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of hydrodynamic connectivity can determine both the assemblage and abundance of organisms in wetlands (Meynecke et al 2008; Fernandes et al 2015). The breaches at Blacklock provide considerable exchange with the adjacent embayment through which aquatic organisms can enter and leave the restoring marsh.…”
Section: Discussionmentioning
confidence: 99%
“…The past 20 years has seen the expansion of intensive agriculture practices in the floodplain and a coincident collapse of littoral species that exploit the floodplain during their early‐life history stages. As intensive agriculture practices are known to alter natural habitats and impede connectivity in the floodplain (e.g., Fernandes et al ), an effort to better understand the impact of altered connectivity is needed to initiate management actions to restore species’ abundance. The present study has shown that conditions favoring early‐life history recruitment require not only quality spawning and nursery habitats but also the environmental conditions allowing eggs to hatch and larvae to reach nurseries.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the spatial factor (MEM2) may be related to the limited dispersal capacity of small-sized fish species at larger scales (Griffiths 2006;Bie et al 2012;Henriques-Silva et al 2013;Fernandes et al 2014). Small fish are mostly short-distance migrants, and respond mainly to fine-scale environmental variations like water depth and habitat structure (Lamouroux et al 1999;Fernandes et al 2015). Likewise, the effect of the distance from headwaters also points to limited dispersal capacity, as predicted by the network position hypothesis (Henriques-Silva et al 2019;Borthagaray et al 2020).…”
Section: Effect Of Environmental and Spatial Factors On Fish Assemblagesmentioning
confidence: 99%
“…Small-sized fish are found mainly in marginal regions associated with aquatic vegetation, where a complex habitat structure composed by leaves, stems and roots provides suitable shelter and food (Dias et al 2011). Besides this, small-sized fish need a small area to complete their life cycle (Agostinho et al 2007b), and respond to fine-scale environmental variations rather than to spatial factors (Fernandes et al 2015).…”
Section: Introductionmentioning
confidence: 99%